Research progress and clinical experience of Banxia Xiexin Decoction in the treatment of insomnia - Shi-Heng Wang (Editorial Board of Journal of Hainan Medical University, 2021)
Insomnia is a common clinical disease. At present, with the increase of work and life pressure, the incidence of insomnia is increasing year by year, which seriously affects people's physical and mental health and quality of life. Although stable drugs are effective in the treatment of insomnia, they have long-term side effects. Traditional Chinese medicine has unique advantages in the treatment of insomnia. Among them, Banxia Xiexin Decoction is based on the theory of "stomach disorder, sleep restlessness". Curative effect. By searching relevant literature, this article discusses the research progress of Banxia Xiexin Decoction in the treatment of insomnia from the theory, prescription and clinical research of Banxia Xiexin Decoction, and describes the clinical experience of using Banxia Xiexin Decoction. In order to provide some reference for the clinic.